Ponderosa Pine Regeneration, Wildland Fuels Management, and Habitat Conservation: Identifying Trade-Offs Following Wildfire - Victoria M. Donovan (Forests, 2019)
Increasing wildfires in western North American conifer forests have led to debates surrounding the application of post-fire management practices. There is a lack of consensus on whether (and to what extent) post-fire management assists or hinders managers in achieving goals, particularly in under-studied regions like eastern ponderosa pine forests. This makes it difficult for forest managers to balance among competing interests. We contrast structural and community characteristics across unburned ponderosa pine forest, severely burned ponderosa pine forest, and severely burned ponderosa pine forest treated with post-fire management with respect to three management objectives: ponderosa pine regeneration, wildland fuels control, and habitat conservation. Ponderosa pine saplings were more abundant in treated burned sites than untreated burned sites, suggesting increases in tree regeneration following tree planting; however, natural regeneration was evident in both unburned and untreated burned sites. Wildland fuels management greatly reduced snags and coarse woody debris in treated burned sites. Understory cover measurements revealed bare ground and fine woody debris were more strongly associated with untreated burned sites, and greater levels of forbs and grass were more strongly associated with treated burned sites. Wildlife habitat was greatly reduced following post-fire treatments. There were no tree cavities in treated burned sites, whereas untreated burned sites had an average of 27 ± 7.68 cavities per hectare. Correspondingly, we found almost double the avian species richness in untreated burned sites compared to treated burned sites (22 species versus 12 species). Unburned forests and untreated burned areas had the same species richness, but hosted unique avian communities. Our results indicate conflicting outcomes with respect to management objectives, most evident in the clear costs to habitat conservation following post-fire management application.